2011
DOI: 10.1038/ng.841
|View full text |Cite
|
Sign up to set email alerts
|

The splicing regulator Rbfox1 (A2BP1) controls neuronal excitation in the mammalian brain

Abstract: The Rbfox family of RNA binding proteins regulates alternative splicing of many important neuronal transcripts but their role in neuronal physiology is not clear1. We show here that central nervous system (CNS)-specific deletion of the Rbfox1 gene results in heightened susceptibility to spontaneous and kainic acid-induced seizures. Electrophysiological recording reveals a corresponding increase in neuronal excitability in the dentate gyrus of the knockout mice. Whole transcriptome analyses identify multiple sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
371
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(403 citation statements)
references
References 48 publications
17
371
2
Order By: Relevance
“…The similar phenotype observed for Rbfox1 and Rbfox2 KD suggests that both RBPs regulate overlapping sets of transcripts in beta cells. This is in agreement with previous studies showing that Rbfox proteins bind to the same UGCAUG motif due to the presence of a common RNA binding domain (28,32,62). Functional analysis of the role of Rbfox proteins in beta cells (present data) indicates that Rbfox depletion increases the insulin secretory capacity by affecting actin depolymerization kinetics following glucose stimulation.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 82%
See 1 more Smart Citation
“…The similar phenotype observed for Rbfox1 and Rbfox2 KD suggests that both RBPs regulate overlapping sets of transcripts in beta cells. This is in agreement with previous studies showing that Rbfox proteins bind to the same UGCAUG motif due to the presence of a common RNA binding domain (28,32,62). Functional analysis of the role of Rbfox proteins in beta cells (present data) indicates that Rbfox depletion increases the insulin secretory capacity by affecting actin depolymerization kinetics following glucose stimulation.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 82%
“…Our data analysis identified a cluster of RBPs that are expressed in both brain and in human islets. This cluster includes members of the Elavl, Nova, and Rbfox families, which have been implicated in neuronal physiology and disease (28,(31)(32)(33)(34)(35). We found that Elavl4 and Nova2 are required for beta cell survival, and their depletion leads to activation of the intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 84%
“…Mutations or deletions in RBFOX1 and RBFOX3 are found in epilepsy patients (Bhalla et al 2004;Lal et al 2013a,b), whereas copy-number variations in RBFOX1 are associated with autism spectrum disorders and spinocerebellar ataxias (Bill et al 2013;Weyn-Vanhentenryck et al 2014). Mouse models with Rbfox KO or KD show extensive defects in neuronal and muscle physiology, suggesting that these proteins play key roles in normal development (Gehman et al 2011(Gehman et al , 2012. A role for RBFOX2 in cancer has also been proposed.…”
Section: Rbfox2-rna Binding Protein Fox-2 Homologmentioning
confidence: 99%
“…6C; Supplemental Table S4). The GO term enrichment profile for PQBP1's AS targets is specific compared with high-throughput studies on other proteins in neurons, especially RNA splicing, chromatin modification, dendrite development-related functions, and ARF signal transduction (Ule et al 2005;Gehman et al 2011;Charizanis et al 2012). Bcl-x AS is not conserved from humans to mice and was not identified as a target in this analysis.…”
Section: Coupling Of Neuron Projection and Pqbp1 Functionmentioning
confidence: 99%